Factors Related to The Implementation of Early Breastfeeding by Midwives at Datu Sanggul Rantau Hospital - M Riduan Abriadi; Husaini Husaini; Eko Suhartono; Zairin Noor; Meitria Syahadatina Noor (Jurnal Berkala Kesehatan, 2021)
Early initiation of breastfeeding is program of Indonesian Government.   Early breastfeeding has not been widely practiced, <30% for South Kalimantan and 21% for Tapin District. The implementation of early initiation of breastfeeding by midwives at Datu Sanggul Rantau Hospital is influenced by age, education level, years of service, midwife training and socialization of implementation of early breastfeeding initiation. This study aims was to analyze the factors associated with implementation of early initiation of breastfeeding by midwives at Datu Sanggul Rantau Hospital. The study was cross sectional, with 32 midwives in PONEK, maternity and nicu at Datu Sanggul Rantau Hospital. The variables were age, education level, years of service, training and socialization. Data were analyzed using Chi square.  The results showed socialization was related with p value of 0.004. Unrelated factors were age p value 0.660, education level p value 0.496, years of service p value of 0.761, and training p value 0.314. Simultaneously, age, education level, years of service, training and socialization are not related to the implementation of early breastfeeding initiation with p value 0, 083. The conclusion is there is a significant relationship between socialization and the implementation of early initiation of breastfeeding at Datu Sanggul Rantau Hospital.